Analysis Of Risk Factors Of Mellitus Diabetes At Hospital H. Andi Sulthan Daeng Radja Bulukumba - Hardianti; Haerani; Amirullah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
Diabetes Mellitus (DM) is a health disorder in the form of a collection of symptoms caused by an increase in blood sugar (glucose) levels due to insulin deficiency or resistance. DM can cause complications such as hypertension, myocardial infarction, coronary insufficiency, diabetic retinopathy, cataracts, diabetic neuropathy, and others. Factors associated with diabetes mellitus are gender, age, genetic factors, obesity, hypertension, stress, cholesterol levels, and diet. From the results of a preliminary study conducted by researchers on July 25, 2018, with as many as 80 respondents, 40 respondents who experienced DM and 40 respondents who did not experience DM. The purpose of this study was to determine the factors associated with the incidence of diabetes mellitus in H.Andi Sulthan Hospital Daeng Radja Bulukumba in 2018 This study uses analytical design with a